MORPHOLOGY OF SPRAY DRIED RED PITAYA - Ruri Aditya Sari; Norziah Mohd. Hani Mohd. Hani; Kinanti Wijaya (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
Betacyanin pigments from red pitaya fruit (Hylocereus polyrhizus) could be an alternative source of natural red colourant for food application. The extraction of betacyanin pigment was extracted from the flesh of red pitaya fruits grown locally in Malaysia by using water as the extracting solvents. Spray-drying technique was also performed on the pigment extracts to increase the stability and shelf life of the pigment extracts obtained. Two types of maltodextrin with different DE’s (10 DE and 25 DE) and mixtures (10 DE + 25 DE) were used as coating agents in the spray drying technique to give a total soluble solid (TSS) ranging from 20 % - 30 %. The objective of this study was to investigate the effect of different types of maltodextrin on the morphology of pigment powder. The morphology of the red pitaya pigment powders produced at drying temperatures (200 ˚C) in the spray drying technique were characterized by using Scanning Electron Microscopy. The morphology of pigment powders upon storage (0 - 6 months) with the ascorbic acid (0.1 % and 1.0 % w/w, respectively) addition was also investigated. Maltodextrin 25 DE had smoother outer structures when compared to 10 DE. The SEM micrographs showed that 10 DE samples had more surface indentations and cracks in wall system. Keywords: pigment, red pitaya, spray dry, SEM